Administration of unclaimed estates in Malaysia: the peculiarities of unclaimed money, undistributed fund and bona vacantia - Halim, Akmal Hidayah; Mohd Noor, Nor Azlina; Arshad, Azhani (Academic Research Publishing Group, 2018)
Issues relating to the complexities of unclaimed estates have become a national concern and a major recurring problem as the value of such estates is growing annually. However, despite the constant reports on the increasing value of unclaimed estates, it is very unfortunate that the exact types of unclaimed estates remain hitherto uncertain and not specifically identified. Hence, this paper aims to examine the peculiarities of unclaimed estates in the administration of the deceased’s estate in Malaysia. The main focus is to analyse the position of the unclaimed money, the undistributed fund and the case of bona vacantia for the estate of a person dying intestate and leaving no heir to inherit accordingly. The discussion adopts the doctrinal analysis by examining the existing primary and secondary materials including statutory provisions, case law and other legal and non-legal literatures. The paper finds that the existence of various laws that governs different types of unclaimed estates has led to the distinctive methods in the administration and management of such estates. Hence, it is highly important that these types of estates together with legal and procedural mechanisms relating to the administration of such estates are clearly identified so that productive elements of such estates would be activated to the advantage of the rightful beneficiaries.